2018
DOI: 10.3389/fmicb.2018.03197
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Bacterial Communities in Soil and Leachate Water After Swine Manure Application

Abstract: Application of swine manure to agricultural land allows recycling of plant nutrients, but excess nitrate, phosphorus and fecal bacteria impact surface and drainage water quality. While agronomic and water quality impacts are well studied, little is known about the impact of swine manure slurry on soil microbial communities. We applied swine manure to intact soil columns collected from plots maintained under chisel plow or no-till with corn and soybean rotation. Targeted 16S-rRNA gene sequencing was used to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 57 publications
7
29
0
Order By: Relevance
“…This result suggests that soil and manure might be important sources that contribute to the profiles of plant phyllosphere microbiomes (20,42). Manure amendment could directly introduce unique fecal microbes, including antibiotic-resistant bacteria, to arable land and subsequently change the structure of microbiomes and profiles of resistome in the plant phyllosphere (43).…”
Section: Discussionmentioning
confidence: 98%
“…This result suggests that soil and manure might be important sources that contribute to the profiles of plant phyllosphere microbiomes (20,42). Manure amendment could directly introduce unique fecal microbes, including antibiotic-resistant bacteria, to arable land and subsequently change the structure of microbiomes and profiles of resistome in the plant phyllosphere (43).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have found that manure-associated bacteria had only a temporary effect on soil the microbiome and suggested that most manure-associated bacteria are not well adapted to survive in soil [68, 69]. In a microcosm study, Rieke et al found that most manure associated OTUs which elevated in soil after manure application began to decrease in soil after 24 days [70]. However, it is possible that the manure microbiome is instead dispersing to elsewhere in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Manure-treated soil columns were destructively sampled on days 24, 59, and 108. DNA was extracted as previously described in [31]. For every DNA extraction in this study, 4 replicates were taken, totaling 56 samples collected.…”
Section: Methodsmentioning
confidence: 99%